IMPORTANT RESEARCH ON THE MAINTENANCE OF SPEECH AND HUMAN HEALTH (American Journal of Research in Humanities and Social Sciences, 2023)
The article discusses the place and role of the word as an important means of preserving human health in the scientific conclusions of natural scientists of foreign countries, summarizing the results achieved, the effective and appropriate use of the word, revealing the scientific, theoretical and methodological significance of the teaching manual dedicated to solving the actual scientific and philosophical problems of linguistics.